2019
DOI: 10.1111/bcpt.13198
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐national comparison of paediatric antibiotic use in Norway, Portugal and Hungary

Abstract: A cross‐national comparison was performed on paediatric (0‐19 years) antibiotic use in Hungary, Norway and Portugal to explore and compare the scale and pattern of paediatric antibiotic use in these three European countries. Ambulatory care systemic antibiotic use (ATC: J01) was retrieved from national databases for year 2014. The main outcome measure was number of antibacterial packages per child inhabitant per year (packages/child/year) and was further stratified by age groups. Paediatric antibiotic use peak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 30 publications
1
10
0
1
Order By: Relevance
“…A more recent study from Hungary, Norway and Portugal identified antibacterial use as packages/child/ year in 2014 with children age 0-19, stratified by age groups. This study identifies the youngest children (0-4 years) as the most frequent users of antibacterials, with respectively 2.2, 0.4 and 1.0 packages/child/year in Hungary, Norway and Portugal (29). The results from Norway are on par with our results, even though we are using different age stratification and proxy-measure for antibacterial use.…”
Section: Discussionsupporting
confidence: 57%
“…A more recent study from Hungary, Norway and Portugal identified antibacterial use as packages/child/ year in 2014 with children age 0-19, stratified by age groups. This study identifies the youngest children (0-4 years) as the most frequent users of antibacterials, with respectively 2.2, 0.4 and 1.0 packages/child/year in Hungary, Norway and Portugal (29). The results from Norway are on par with our results, even though we are using different age stratification and proxy-measure for antibacterial use.…”
Section: Discussionsupporting
confidence: 57%
“…On the contrary, a cross-national analysis on antibiotic use in children of 6 countries found that [40], in the United States, South Korea, Italy, Spain, and Norway, penicillins were the most common prescribed antibiotics. In US and Norway [40,41], if a penicillin was prescribed for pediatrics, the narrow-spectrum penicillins were commonly used. According to the Chinese Pharmacopeia Guidelines for Clinical Drug Use, penicillins require skin tests before use in China, which largely limits the use of penicillins in our country.…”
Section: Discussionmentioning
confidence: 99%
“…The observed prescription rate in German children (0–14 years) of 428 prescriptions per 1,000 persons in 2018 was considerably lower than in Italian children in 2016 (881/1,000 [ 33 ]) and lower than the package rates from Hungary (1,386/1,000) and Portugal (838/1,000) in 2014, but more than 70% higher than package rates from Norway (236/1,000 in 2014) [ 18 ] and the Netherlands (247/1,000 in 2016) [ 17 ]. Of note, the package rates for Hungary, Portugal and Norway reported here for the age group 0–14 years were calculated based on the age-specific numerator and denominator data that can be found in Benko et al [ 18 ], who included the age group 0–19 years in their study. The strong variations among European countries are unlikely to reflect an actual therapeutic need originating in marked inter-country differences in the burden of infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, use of cephalosporins in children and the total population is negligible in Scandinavian countries, the Netherlands and the United Kingdom [ 6 , 17 , 18 , 37 ]. While German clinical practice guidelines for the outpatient treatment of acute respiratory infections commonly recommend cephalosporins as second- or third-line treatment [ 8 , 26 ], these antibiotics are not mentioned as treatment option by Dutch guidelines [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation